ChemInform Abstract: Synthesis of Unsymmetrical Diorganyl Chalcogenides under Greener Conditions: Use of an Iodine/DMSO System, Solvent‐ and Metal‐Free Approach. Issue 36 (September 2015) - Saba, Sumbal; Rafique, Jamal; Braga, Antonio L.
Abstract The use of iodine as the catalyst and DMSO as the oxidant renders possible the coupling of diorganyl dichalcogenides with arylboronic acids and vinyltrifluoroborate (VIII) to give the title products in good yields.